Stability Constants of UO2(II) Complexes with Substituted 1,2,4-Triazoles - Ramana, V.V.; Yamuna, K.; Saraswathi, K. (Asian Journal of Chemistry, 2010)
The proton-ligand dissociation constants of certain substituted 1, 2, 4-triazoles and the stability constants of their metal complexes with UO2(II) in 60% ethanol-water medium at 28ºC using Bjerrum Calvin pH titration technique as modified by Irving and Rossotti were reported.